Mitigation Scenario of Beef Cattle Greenhouse Gas Emission In Developing Country: A System Dynamic Approach - Nurbani, Muhammad Fauzan; Suryani, Erma (IJISTECH (International Journal of Information System and Technology), 2023)
Ever increasing beef demand and government desire to fulfill it has built stress on beef production system. The system then tries to increase it production capacity by increasing cattle population. This leads to the increment of greenhouse gas emission. Specifically, cattle dominate 65% of greenhouse gas emission from agricultural activity. With the densest beef cattle population, East Java have the biggest amount of green house gas emission from beef cattle in Indonesia. The purpose of the research is to find out what mitigation is the most effective to reduce this emission. A model of green house gas emission from beef cattle developed using system dynamic approach. It includes stages such as problem articulation, development of dynamic hypothesis, simulation model formulation, model validation and scemario development. Secondary data from previous researches are used in the model development. Several mitigation scenarios then developed and applied to the model. According to the model developed, emission can be reduced by implementing feed additive. Natural feed additive is used on the model instead of syntetic chemical. This mitigation scenario is able to reduce overal greenhouse gas emission by 4% by adding 15% of Acacia mangnium leaves to the feed. Model and scenatio can be used by stakeholders as reference to mitigate green house gas emission from beef cattle.